2012
DOI: 10.1080/02626667.2012.659250
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Ocean sea-surface temperatures and regional streamflow variability in the Adour-Garonne basin, France

Abstract: The identification of Atlantic Ocean (AO) climatic drivers may prove valuable in long lead-time forecasting of streamflow in the Adour-Garonne basin in southwestern France. Previous studies have identified the Atlantic Multidecadal Oscillation (AMO) and the North Atlantic Oscillation (NAO) as drivers of European hydrology. The current research applied the singular value decomposition (SVD) statistical method to AO sea-surface temperatures (SSTs) to identify the primary AO climatic drivers of the Adour-Garonne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Regarding rivers flows over France, to the best of our knowledge, such large and widespread multidecadal variations have not been described before. The links between SST averaged in the North Atlantic (called AMO in those studies but probably best called the North Atlantic SST (NASST) index as those studies do not specifically deal with multi-decadal variations) and river flows in France have been studied by Oubeidillah et al (2012) and Giuntoli et al (2013). Other than at a few gauging stations, Oubeidillah et al (2012) report no significant relationships between NASST and river flows in the Adour-Garonne Basin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding rivers flows over France, to the best of our knowledge, such large and widespread multidecadal variations have not been described before. The links between SST averaged in the North Atlantic (called AMO in those studies but probably best called the North Atlantic SST (NASST) index as those studies do not specifically deal with multi-decadal variations) and river flows in France have been studied by Oubeidillah et al (2012) and Giuntoli et al (2013). Other than at a few gauging stations, Oubeidillah et al (2012) report no significant relationships between NASST and river flows in the Adour-Garonne Basin.…”
Section: Discussionmentioning
confidence: 99%
“…The links between SST averaged in the North Atlantic (called AMO in those studies but probably best called the North Atlantic SST (NASST) index as those studies do not specifically deal with multi-decadal variations) and river flows in France have been studied by Oubeidillah et al (2012) and Giuntoli et al (2013). Other than at a few gauging stations, Oubeidillah et al (2012) report no significant relationships between NASST and river flows in the Adour-Garonne Basin. Giuntoli et al (2013) show significant relationships between hydrological drought severity at some gauging stations over France and the NASST index.…”
Section: Discussionmentioning
confidence: 99%
“…Also focusing on stream flow drought, but for winter multiannual events for the English lowlands, Folland et al (2015) have shown that La Nina episodes, through producing winter rainfall deficits, are important for some multi-annual stream flow and groundwater drought episodes; stream flow drought indicators also show some evidence of weak links to ENSO as well. For stream flow variability in the Adour-Garonne basin in south western France, Oubeidillah et al (2012) identified SST anomalies in the equatorial region of the Atlantic Ocean to be important as well as the AMO and NAO. Remote connections between stream flow and SST are also evident for some river basins in Africa.…”
Section: Stream Flowmentioning
confidence: 98%
“…Most studies since then, including the very recent ones, have scrutinized the multidimensional role of specific oceanic-atmospheric phenomena, such as ENSO, Equatorial Indian Ocean Oscillation (EQUINOO), Pacific Decadal Oscillation (PDO), Atlantic Multidecadal Oscillation (AMO), Indian Ocean Dipole (IOD), North Atlantic Oscillation (NAO), etc. in influencing hydrological variables worldwide (Chiew and McMahon 2002, Terray et al 2003, Gadgil et al 2004, Goswami et al 2006, Maity and Nagesh Kumar 2006, 2008, Feng and Hu 2008, Li et al 2008, Mo and Schemm 2008, Ting et al 2011, Singhrattna et al 2012, Oubeidillah et al 2012, Jiang et al 2013, Rogers 2013, Wang et al 2013. For instance, the influence of ENSO and AMO has been established in relation to the variability of China's summer precipitation (Gu et al 2009, Ye 2014 as well as the frequency of its extreme precipitation events (Fu et al 2013).…”
Section: Introductionmentioning
confidence: 99%